Child Involvement in Family Financial Management and Subjective Well-Being of Children from the Intact and Non-Intact Families - Leti Nurhayati; Istiqlaliyah Muflikhati (Journal of Consumer Sciences, 2020)
The purpose of this research is to analyze the influence of child involvement in family financial management and material well-being on children’s subjective well-being among children from intact families and non-intact families. Fifty students from intact families and fifty students from the non-intact family have participated in this research. The students were selected using stratified random sampling techniques from junior high schools in Bogor Regency. Data were collected using a self-administered questionnaire and were followed with in-depth interviews with some students. The result of this research showed that child involvement, material well-being, and subjective well-being were categorized as medium. The result of the independent sample T-test showed that there were no significant differences between students from intact families and students from non-intact families in terms of their involvement in family financial management, material well-being, and subjective well-being. The result of the multiple linear regression test showed that child involvement in family financial management significantly positively affected their subjective well-being. Thus, the higher the children involved in family financial management, the better their subjective well-being.